Crown Dimensions of Deciduous Teeth: The Tool for Predicting the Physical Height of the Child: A Pilot Study - Siddhi Nilesh Savla; Swati Shrikant Gotmare; Treville Pereira; Mandavi Waghmare; Sushma Sonawane; Tanmik Shah; Anish Gupta; Nithi Rajadhyaksha (Journal of Clinical and Diagnostic Research, 2018)
Introduction: Dental profiling is one of the well known methods in forensic sciences that help in identification of disaster victim. In forensic sciences there are many techniques used for personal identification which give definite results. As adult height estimation can be done by measuring the dimensions of the long bones of hand, foot and vertebral column, similarly stature of the child can be estimated using tooth dimension. Aim: To evaluate the relationship between height of the child and the clinical crown length of deciduous teeth. Materials and Methods: The sample size used in the present study was 30, comprising of 15 boys and 15 girls which ranged in the age group of 3-6 years. The clinical crown length of tooth numbers-51, 52, 53, 54, 55 were measured with the help of Vernier calliper and standard measuring tape was used to measure the height of the child. Ratios of the crown length and height were calculated. Student’s unpaired t-test and Pearson’s correlation coefficient was used to evaluate the relationship between the tooth crown length and height of the child. Results: Significant values were obtained in tooth numbers-52 in combined samples, 51 and 52 in male samples and 53 in female samples. Mean height of the crown in male patients with respect to tooth number 51, 52, 53, 54 and 55 were found to be 5.89, 4.77, 5.94, 4.55, and 4.18 respectively. However, the mean height of the individuals was found to be 942.84 mm. The mean height of crown in females was 5.02, 4.53, 5.31, 4.76 and 4.68 respectively while their mean height was found to be 1001.77 mm. Conclusion: As per the present study, clinical crown length of anterior teeth (51, 52) in males can be used for predicting the physical height of the child and clinical crown length of canines (53) in female can be used for predicting the physical height of the child with caution. For more significant results, further studies should be done with a larger sample size.